2021
DOI: 10.1002/ar.24783
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupuncture in the treatment of depression: A systematic review of clinical research

Abstract: As a common mental disorder, depression is one of the leading causes of disability around the world. Clinical studies have shown that acupuncture is an effective therapy without obvious side effects compared to limited efficacy and adverse reactions of drug therapy, cognitive behavioral therapy, and neuromodulation technology in treating depression. The objective of this review is to systematically evaluate whether acupuncture therapies for depression are safe and effective in order to provide a high-quality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…An early study demonstrated that manual stimulation of the Kl 3 acupoint influenced significantly peripheral vascular circulation, by means of sympathetic stimulation causing vasoconstriction [30]. Acupuncture is widely used in clinical practice and had been shown to have antidepressant effects in both clinical and animal studies [7,8,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…An early study demonstrated that manual stimulation of the Kl 3 acupoint influenced significantly peripheral vascular circulation, by means of sympathetic stimulation causing vasoconstriction [30]. Acupuncture is widely used in clinical practice and had been shown to have antidepressant effects in both clinical and animal studies [7,8,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The theory of “healing spirit” is used throughout the treatment process, and the therapeutic effect is achieved by regulating the body’s qi, blood, yin, and yang. A large body of evidence suggests that acupuncture has satisfactory efficacy and safety in the treatment of depression ( 6 , 31 , 32 ) and CVD ( 33 35 ). Experiments in animal models of depression have shown that acupuncture increases hippocampal and neuroplasticity, reduces brain inflammation, and has effects on the HPA axis, neuropeptides, and neurotransmitters ( 34 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a traditional Chinese therapy that has been used to treat mental disorders since ancient times. Current research provides some evidence for the use of acupuncture for depression 12 13. Some of the studies that reported these beneficial effects suggested that the mechanisms might include the direct or indirect modulation of activity and connectivity of key brain regions that function in depression and mood regulation.…”
Section: Introductionmentioning
confidence: 99%